Kebijakan Dan Strategi Pengelolaan Manajemen Modal Kerja - Christian Herdinata; Cliff Kohardinata; Meidiahna Kusuma (BIP's JURNAL BISNIS PERSPEKTIF, 2017)
Working capital (capital) ie cash, accounts receivable, inventory. Companies follow a working capital cycle. Some things related to this are: (1) the cash conversion cycle is how much time the funds are tied up in working capital or how much time between the payment for working capital and cash collection from the sale of working capital (Brigham and Houston, 2014 ); (2) the average collection period is the average time required to convert raw materials into finished goods and sell them (Brigham and Houston, 2014); (3) the average collection period is the average time required to change a company's receivables into cash or to collect cash after a sale; (4) the payable period (payables deferral period) is the average time between the purchase of raw materials and labor with cash payments. The results of this study explain the strategies and policies that can be used in medium-sized businesses.